Tanggung Jawab Perusahaan PT Surya Sawit Mandiri Dalam Perbuatan Melawan Hukum Di Desa Koto Tandun Kabupaten Rokan Hulu - Fitriyani, Fitriyani; Ismi, Hayatul; Darnia, Meriza Elpha (Jurnal Ilmiah Wahana Pendidikan, 2025)
Unlawful acts are actions that violate the rights or interests of other people which are protected by law. in unlawful acts, the perpetrator is asked to e held responsible. This rasearch aims to analyze the responsibility of PT Surya Sawit Mandiri for unlawful acts that occured in Koto Tandun Village, Rokan Hulu Regency. The main focus is the impact of environmental pollution caused by this company’s activities, including air and water pollution, as well as the impact on the health of local communitaies. Apart from that, researshers also examine the obstacles faced by companies in completing their responsibilities. The type of research used by the author is sociological research, because in this research the author directly conducted research at the location or place being studied in order to provide a complete and clear picture. This research was conducted in Koto Tandun Village, Rokan Hulu Regency, while the population and sample were all parties related to the company and the supporting literature. The data obtained was then analyzed qualitatively and preseted descriptively. Based on theresearch results, it was found that PT Surya Sawit Mandiri dit not fully comply with applicable rules and regulations, causing harm to the community and the surrounding evironment. However, PT Surya Sawit Mandiri wil take quite a long time due to the many obstacles it faces. For this reason, it is hoped that this research can provide suggestions for increasing company compliance with environmental regulations and managing negative impacts arising from inustrial activities.